Seroprevalence of NMO-IgG antibody in Brazilian patients with neuromyelitis optica - Adoni,Tarso (2008)
OBJECTIVE: To determine the seroprevalence of neuromyelitis optica antibody (NMO)-IgG in Brazilian patients with clinical diagnosis of relapsing neuromyelitis optica, also known as Devic's disease. METHOD: We determined NMO-IgG titers in 28 patients (25 of them females) that fulfilled the 1999 NMO diagnostic criteria proposed by Wingerchuk et al. RESULTS: NMO-IgG was detected in 18 NMO patients (64.3%). CONCLUSION: Our results showed that seroprevalence of NMO-IgG in Brazilian NMO patients was similar to the observed in other studies.